Pengaruh, Modal Sosial, Kualitas Informasi, dan Kompetensi Pemasaran terhadap Kinerja Pemasaran (Studi pada Industri Kecil dan Menengah Garmen di Jawa Timur) - Nurita Andriani; Djumilah Zain (Jurnal Aplikasi Manajemen, 2012)
The study on resource related to the strategy and performance usually focuses on human, financial, and physical capital resources. However, since the resources mentioned above are easily imitated, they rarely put the company in long lasting competitiveness advantage. This promotes a quest to search the most probable resources to be the company competitiveness advantage. The quest results in the unique company resources built inside its social environment called social capital. The social capital built by the company will affect the quality of acquired information used for developing the marketing competence. Studies on marketing competences generally were unspecific. Therefore, based on the research opportunity, this research is to test and prove empirically whether the social capital, information quality, marketing intelligence, and marketing innovation influence the marketing performance. This study also aims to prove whether marketing intelligence and innovation were the dominant factors in marketing performance.. The result of the study showed that commitment is the most important factor in building the social capital. The nurturing of social capital can increase the information quality acquired and the marketing performance. Through the high-grade information quality, the social capital will increase both marketing intelligence and innovation. Marketing intelligence is dominant marketing competence in increasing marketing. Information quality has yet to contribute directly to the marketing performance, however, the marketing intelligence and innovation can support the development of marketing performance.Keywords: Social Capital, Marketing Information Quality, Marketing Intelligence, Marketing Innovation, Marketing Performance.